Great powers and regional orders the United States and the Persian Gulf - Kaim, Markus 1968- (US foreign policy and conflict in the Islamic world series)
Great Powers and Regional Orders explores the manifestations of US power in the Persian Gulf and the limits of American influence. Significantly, this volume explores both the impact of US domestic politics and the role played by the region itself in terms of regional policy, order and stability. Well organized and logically structured, Markus Kaim and contributors have produced a new and unique contribution to the field that is applicable not only to US policy in the Persian Gulf but also to many other regional contexts. This will interest anyone working or researching within foreign policy, US and Middle Eastern politics.